2013
DOI: 10.1021/jf302135k
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Thermal Decomposition of Starch and Cellulose in Model Systems and Toasted Bread Using Domino Tandem Mass Spectrometry

Abstract: Many dietary products containing polysaccharides, mostly starch and cellulose, are processed by thermal treatment. Similarly to the formation of caramel from mono- and disaccharides, the chemical structure of the carbohydrates is dramatically altered by heat treatment. This contribution investigates the products of thermal decomposition of pure starch and cellulose as model systems followed by an investigation of bread obtained at comparable conditions using a combination of modern mass spectrometry techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Only, exothermic signals which were likely due to the oxidation decomposition processes of the studied materials were appeared. The FTIR spectrum of the gases extracted at T max2 is a typical gases spectrum for starch decomposition products in oxidative conditions, which is in agreement with the literature data [1][2][3][4][5][6]. However, on the FTIR spectrum gathered at T max2a , one can see mainly the emission of CO 2 (bands at the wavelength of approx.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Only, exothermic signals which were likely due to the oxidation decomposition processes of the studied materials were appeared. The FTIR spectrum of the gases extracted at T max2 is a typical gases spectrum for starch decomposition products in oxidative conditions, which is in agreement with the literature data [1][2][3][4][5][6]. However, on the FTIR spectrum gathered at T max2a , one can see mainly the emission of CO 2 (bands at the wavelength of approx.…”
Section: Resultssupporting
confidence: 89%
“…Generally, different, simultaneous phase transformations under the heating of starch happen. The most significant of all are melting, evaporation, sublimation, chemical condensation, decomposition and carbonization leading to the creation of the mixture of volatiles [1][2][3][4][5][6]. Due to the availability of starch, its low cost and the presence of hydroxyl groups in its structure, it can be chemically modified and thus different structure starch graft copolymers with potential applications as fillers, stabilizers, impact resistant materials, plastics, modifiers, matrices, excipients, etc., can be prepared.…”
Section: Introductionmentioning
confidence: 99%
“…In resume, the MS data showed that the dry heating of OS and PS samples caused not only depolymerization but also dehydration, effects which are described in the literature for similar compounds (Chiku, Nishimoto, & Kitaoka, 2010;Čmelík & Chmelík, 2010;Golon, González, Dávalos, & Kuhnert, 2013). In the case of OS samples, it was also able to induce polymerization (Moreira et al, 2011) and confirmed by Golon & Kuhnert (2012).…”
Section: Esi-ms Of Ps After Thermal Treatmentmentioning
confidence: 55%
“…However, the thermal decomposition of starches from different botanical origins showed no significant relationship between microstructure (crystallinity, granule size) and the thermal degradation process (Guinesi et al., 2006). Dehydrated oligomers of glucose and individual molecules of dehydrated glucose are the predominant products of thermal decomposition of pure starch in model systems and in toasted bread (Golon et al., 2013). Sugars and oligomers released by thermal degradation as well as simple sugars resulting from amylolytic activity on (damaged) starch may be involved in the Maillard reaction during the above heat treatments (De Noni and Pagani, 2010).…”
Section: Effects Of Processing On Structure and Compositionmentioning
confidence: 99%